Significance of Written Sources in the Study of Historic-Archaeological Heritage of Ganja City - Elnur Hasanov (Maddah: Journal of Advanced Da'wah Management Research, 2025)
The main aim of the scientific paper is investigation of archival materials, their great importance in the study of the historical past, also archaeological heritage of Azerbaijan, also the ancient city Ganja. Especially the archives as one of the main sources have so much rich information about the period of Ganja khanate. The documents of the archive are important historical sources in the study of material culture of Azerbaijan during this historical period – the late Middle ages. For the first time various written documents such as the archival sources, archaeological materials for the late seventieth – early eighteens centuries ages have been investigated as the important springs in study of historic-cultural and archaeological heritage of Ganja city. Information about fortress walls, palaces, caravanserais, baths, houses, bridges and other buildings of Azerbaijani cities is preserved in the archive. There are many documents in the archive about the history of Ganja khanate. The official military documents of contain detailed historical information about the economy, culture, demography and political history of the city of Ganja and the khanate. The materials in the funds of different archives, together with other sources of the researched period, allow to objectively illuminating the study of the history, also cultural heritage of the Ganja Khanate and this ancient city.